Improving Students’ Argumentative Writing through Genre-Based Approach Integrated with Mentimeter in EFL Senior High School Classrooms - Nidyanti Ruwaina; Achmad Yudi Wahyudin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the effectiveness of integrating the Genre-Based Approach (GBA) with Mentimeter to enhance Indonesian EFL senior high school students’ argumentative writing competence. The participants were 36 eleventh-grade students who took part in a one-group pretest–posttest design. Students’ essays were evaluated in five aspects content, organization, vocabulary, language use, and mechanics while their perceptions were collected through a validated five-point Likert-scale questionnaire. The paired-sample t-test result (t = 27.997, p < .001) revealed a statistically significant improvement in overall writing performance, confirming that the integration of GBA and Mentimeter produced a strong positive instructional effect. Students also reported highly favorable perceptions toward the integrated approach, emphasizing that it enhanced their clarity of ideas, engagement, collaboration, motivation, and confidence during writing activities. This research fills the gap in empirical studies exploring technology-supported genre pedagogy within Indonesian EFL contexts, where such integrations are rarely examined in depth. The findings suggest that combining structured genre instruction with interactive digital platforms can foster both cognitive and affective dimensions of writing development. Therefore, the integration of GBA and Mentimeter offers valuable pedagogical implications for English teachers aiming to apply process-oriented, student-centered, and technology-enhanced approaches to improve students’ argumentative writing performance and promote long-term language learning achievement.